The Relationship Between Nutritional Status and The Quality of Life of Chronic Kidney Disease Patients Undergoing Hemodialysis - Collein, Irsanty; Hafid, Fahmi; Ismunandar, Ismunandar (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Patients undergoing hemodialysis for a period of more than 3 years tend to experience malnutrition due to inadequate food intake, diseases of the digestive tract, eating restrictions, drugs that cause impaired nutrient absorption, inadequate dialysis, and comorbidities. This study aimed to determine the relationship between nutritional status and the quality of life of chronic kidney disease patients undergoing hemodialysis in Palu. This study used a cross-sectional design to determine the correlation or relationship between 2 variables. Data were analyzed using the Pearson correlation test. The sampling formula determined the number of samples to test the hypothesis on the average of two populations with 108 respondents. This study was carried out in 2 hemodialysis units in Palu. The samples involved in this study were selected by simple random sampling. The results of this study show that most respondents are in the age range of > 55 years, with 41 people (48.1%); are female, with 56 people (51.9%); have a high school education, with 46 people (42.6%); are working, with 81 people (75%) while the remainings are retirees and housewives; and have hypertension as their comorbid disease, with 56 people (51.9%). There is a relationship between nutritional status and overall quality of life, based on the SGA p-value of 0.016 (p-value < 0.05) and based on the MIS p-value of 0.004 (p-value < 0.05), with the strength of the relationship being weak. The conclusion is there is a relationship between nutritional status and the quality of life of CKD patients undergoing hemodialysis. It is hoped that nurses can pay more attention to the nutritional status of CKD patients undergoing hemodialysis.